Analisis Unsur Intrinsik dan Ekstrinsik Novel Sunda Rasiah Nu Goreng Patut - Nuraisyah Rahmawati (Jaladri : Jurnal Ilmiah Program Studi Bahasa Sunda, 2024)
A novel is a form of literary work that has intrinsic and extrinsic elements. Rasiah Nu Goreng Patut is one of the phenomenal folk tales circulating in Sundanese society, this story is also known as the Karnadi Bandar Bangkong story. So far there has been no research that has discussed the intrinsic and extrinsic elements of the novel Rasiah Nu Goreng Patut completely. The method used is descriptive qualitative with literature review analysis and reduction techniques. In this analysis, intrinsic elements of the novel were found; synopsis, theme, line/plot, characters and characterization, setting, point of view, and message. Extrinsic elements found; the author's background, community background, and the values ​​contained. It can be concluded that the novel ultimately becomes entertainment that conveys many life lessons.